Challenges and Opportunities With the Use of Hypofractionated Radiation Therapy in Cancer Care: Regional Perspectives From South Korea, Japan, Singapore, and Australia - Tetsuo Akimoto, MD; Hidefumi Aoyama, MD; Melvin L.K. Chua, MBBS, FRCR, PhD, FAMS; Dasantha Jayamanne, MD; Takashi Mizowaki, MD, PhD; Lucinda Morris, MBBS; Hiroshi Onishi, MD; Si Yeol Song, MD; Youssef H. Zeidan, MD, PhD; Ricky A. Sharma, MA, MB, BChir, FRCP, FRCR, PhD (Advances in Radiation Oncology, 2023)
Hypofractionated radiotherapy schedules provide higher per-fraction radiation doses delivered in fewer fractions than conventional schedules. This novel delivery method is supported by a large body of clinical trial evidence across various cancer sites in both curative and palliative settings. Hypofractionation is associated with benefits such as lower costs, improved patient access and increased treatment precision, which has led to its inclusion in various treatment guidelines. Despite this, utilization is not uniform across cancer sites and geographic regions due to reasons such as reimbursement models, nuances in healthcare systems, and professional culture. Key factors to ensure patients benefit from access to high quality radiotherapy include publishing clinical evidence, cross-country collaboration to fill knowledge gaps, reviewing reimbursement models, and improving patient advocacy in treatment decision-making.